2017
DOI: 10.3386/w24014
|View full text |Cite
|
Sign up to set email alerts
|

Daily Price Limits and Destructive Market Behavior

Abstract: for helpful comments and suggestions. We especially thank Zhengjun Zhang and two anonymous referees for constructive comments. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 5 publications
2
29
0
Order By: Relevance
“…Finally, we investigate whether the risen or fallen of the idiosyncratic volatility is associated to the trading activities of institutional or retail investors. Despite Nartea et al (2013) conjecture (do not test) that the idiosyncratic volatility is associated with retail investors due to the dominant retail trading in Chinese stock market, the more recent studies by Chen et al (2019) and Darby et al (2019) demonstrate the destabilizing behaviours of large or institutional investors in Chinese stock market. Following Darby et al (2019), we use the cash flow data from the largest trading group as the proxy for institutional trading, and find the idiosyncratic volatility is significantly associated with large stock price and trading activities of institutional investors.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Finally, we investigate whether the risen or fallen of the idiosyncratic volatility is associated to the trading activities of institutional or retail investors. Despite Nartea et al (2013) conjecture (do not test) that the idiosyncratic volatility is associated with retail investors due to the dominant retail trading in Chinese stock market, the more recent studies by Chen et al (2019) and Darby et al (2019) demonstrate the destabilizing behaviours of large or institutional investors in Chinese stock market. Following Darby et al (2019), we use the cash flow data from the largest trading group as the proxy for institutional trading, and find the idiosyncratic volatility is significantly associated with large stock price and trading activities of institutional investors.…”
Section: Introductionmentioning
confidence: 88%
“…The aggregate idiosyncratic volatility is described as by autoregressive process with regimes shift associated with structural market reforms.In addition, due to the retail dominance in stock trading in Chinese stock market, they also present supportive evidence that the episodic idiosyncratic volatility is associated with retailing trading.The question of whether institutional investors or individual investors are responsible for the changes of idiosyncratic is our key research question in this section. DespiteNartea et al (2013) conjecture that retailing investors might be responsible for the changes of idiosyncratic volatility in Chinese stock market due to the dominance of retail trading, a number of recent studies show the destructive trading behaviour of institutional investors in Chinese stock markets Chen et al (2019). show large investors in Chinese stock markets play the destructive market behaviour from 2012 to 2015 via buying on the day when a stock hits the 10% upper price limit and then sell on the next day Darby et al (2019).…”
mentioning
confidence: 99%
“…Second, Chinese regulators enforced a daily 10-percent rule (see e.g., Chen et al (2018b) for a detailed analysis). Under this rule, each individual stock was allowed to move a daily maximum of 10 percent from the previous closing level in either direction, before triggering a price limit.…”
Section: Shadow-financed Margin Accountsmentioning
confidence: 99%
“…There are very few studies discussing circuit breakers in Chinese financial markets after 2018. Chen et al (2019) confirmed the importance of price limits on individual stock trading and pointed out that 41 out of 58 major countries have applied price limit rules in their equity exchanges. Another paper by Chen et al (2017) constructed a theoretical model to investigate how circuit breakers impact the market when investors trade to share risk.…”
Section: A Review Of Circuit Breakermentioning
confidence: 73%